INTRODUCTION OF ENDEMIC Allium tuncelianum KOLLMAN FROM HOT AND TEMPERATE CLIMATE TO SEMI-ARID CLIMATIC CONDITIONS - Suleyman Kizil; Khalid Mahmood Khawar (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
Allium tuncelianum (Tunceli garlic) is a single cloved important threatened endemic geophyte of high commercial importance that grows scattered on hot temperate mountains under oak trees in the eastern Turkish province of Tunceli. Tunceli garlic is used diversely in salads, foods and in pharmaceutical industry. They also offer a rich choice for their use in rock gardens and landscaping. There is need to develop appropriate agronomic practices for its propagation outside its habitat. In line with this objective, the study optimized planting time (1st September, 15th September and 1st October) of A. tuncelianum on mild alkaline soils under semi-arid climatic conditions of Diyarbakir, Turkey. The results of the study showed positive gain in morphological characteristics such that bulb diameter of the plants changed between 3.43 to 4.60 cm, bulb circumference ranged 14.4 to 16.1 cm and bulb weight had a range of 35.9 and 46.3 g. These results underscore positive effects of early and mid September plantings of Tunceli garlic outside its habitat under semi-arid conditions for economic production with early harvest.